Ontogenetic Changes in Nutrients and Stoichiometry in the Invasive Mosquito, Aedes albopictus (Diptera: Culicidae). Issue 1 (17th November 2022) - Valentine, James C; Yee, Donald A
Abstract: A variety of physiological, morphological, and behavioral changes occur throughout the life cycle of mosquitoes, which can be correlated with a shift from the aquatic to terrestrial environment. Aedes albopictus Skuse is an abundant invasive species from Asia that was introduced into the Americas in the 1980's and is responsible for transmitting several important human disease-causing pathogens. How physiological and anatomical changes within each instar and throughout the developmental stages are related to changes in carbon (C) and nitrogen (N) levels are an unexplored area of mosquito ecology. We hypothesized that these changes as well as stoichiometry (C:N) would vary with instar stage and larval diet. Cohorts of larvae were grown in three different diets: animal only (crickets), plant only (red maple leaves), and a mixture containing both types. Larval instars (1st–4th), pupae, and adults were raised in each diet and were separately analyzed for nutrient content (%C, %N) and stoichiometry (C:N). Significant changes in nutrient values occurred across the life cycle, with C:N values being lower in early instars versus adults or pupae, especially in animal only or mixed diets; few differences were detected in %C or %N across ontogeny. This knowledge may lead to a better understanding of mosquito ecology and pathogen transmission.